First-principles prediction of ferromagnetism in transition-metal doped monolayer AlN. (October 2018) - Wang, Shiyao; An, Yurong; Xie, Congwei; Zhang, Heng; Zeng, Qingfeng
Abstract: Two-dimensional (2D) magnetic materials with large spin polarization and high Curie temperature (Tc ) are essential and indispensable for quantum computation, logic and memory operations, and spintronic devices at nanoscale. In this study, using the first-principles calculations based on the spin polarized density functional theory with the generalized gradient approximation (GGA) plus Hubbard-U corrections (GGA + U), we investigated the magnetic and electronic properties of 2D AlN sheets doped with different atoms of 3d transition metal (TM) elements. Our calculations demonstrate that these TM-doped 2D monolayer AlN sheets are magnetic semiconductors with integer magnetic moment. The magnetic moments of these doped systems originate mainly from the TM atoms, following the Hund's rule and crystal field theory. Furthermore, we find that the magnetic coupling in the Mn- and Ni-doped 2D AlN sheets is ferromagnetic, while the magnetic coupling in the other TM-doped 2D AlN sheets is anti-ferromagnetic. For the ferromagnetic and semiconducting TM-doped monolayer AlN sheets, the calculated Curie temperatures are above 400 K, exceeding that (155 K) of the most-studied dilute magnetic GaMnAs material. Our studies suggest that the Mn- and Ni-doped 2D monolayer AlN sheets would show very promising applications in the spintronic device at nanoscale. Highlights: The 2D monolayer AlN sheets doped by atoms of transition metal elements are magnetic semiconductors. The ferromagnetic coupling in the Mn- and Ni-doped monolayer AlN sheets is explained by the indirect exchange mechanism. The substitution of a transition metal atom for an Al atom can be easier to form under the N-rich condition. For the ferromagnetic and semiconducting TM-doped monolayer AlN sheets, the calculated Curie temperatures are above 400 K.